The Role of Profitability in Mediating the Effect of Capital Structure and Liquidity on Firm Value of Transportation and Logistics Companies Listed on the Indonesia Stock Exchange 2020 until 2024 - Giarti, Giarti; Lie, Darwin; Hendry, Hendry; Simanjuntak, Dahnil Anzar; Rostina, Cut Fitri (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2026)
This study aims to examine the influence of product, price, and promotion on consumer purchase decisions. In an increasingly competitive market, companies must be able to offer products with superior value supported by appropriate pricing strategies and effective promotional efforts to influence consumer decisions. This research employs a quantitative approach, using a structured questionnaire distributed to consumers as respondents. Data analysis was conducted through multiple linear regression to determine the extent to which each independent variable affects purchase decisions.The results reveal that the product variable has a positive and significant impact on purchase decisions, indicating that product quality, features, and suitability with consumer needs strongly shape consumers’ choices. The price variable also significantly influences purchase decisions, suggesting that reasonable pricing aligned with product benefits and consumer purchasing power is a critical factor. Additionally, promotion shows a significant effect on purchase decisions, as clear, attractive, and well-targeted promotional activities can increase consumer interest. These findings highlight the importance of managing product quality, pricing, and promotional strategies simultaneously to improve consumer purchase decisions and strengthen market competitiveness.